Experiences and Lessons Learned in Using Community-Based Participatory Research to Recruit Asian American Immigrant Research Participants - Katigbak, Carina; Foley, Meghan; Robert, Lauren; Hutchinson, M. Katherine (Journal of nursing scholarship, 2016)
Purpose By 2050, the number of international migrants is expected to double from 214 million people. Of these, Asian immigrants are projected to comprise the largest foreign‐born population in the United States by the year 2065. Asian American immigrants experience numerous health disparities, but remain under‐represented in health research. The purpose of this article is to examine the experiences and lessons learned in applying community‐based participatory research (CBPR) principles to access and recruit a sample of Asian American research participants. Approach This article reviews unique barriers to research participation among Asian Americans, describes the principles of CBPR, and provides examples of how these principles were employed to bridge recruitment challenges within a qualitative study. Findings and Conclusions CBPR facilitated greater research participation among a group of immigrant Asian Americans. Researchers must be additionally mindful of the importance of building trusting relationships with their community partners, understanding the significance of shared experiences, considering fears around immigration status, and considering ongoing challenges in identifying and reaching hidden populations. Clinical Relevance Clinicians and researchers can employ CBPR principles to guide their work with Asian immigrant communities and other under‐represented groups to facilitate access to the population, improve participant recruitment, and foster engagement and collaboration.